Pengembangan Lembar Kerja Praktikum Scientific Menggunakan Model Problem Based Learning pada Pengukuran Daya 1 Fasa Menggunakan 3 Voltmeter - Muhammad Fuadunnazmi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
Instrumentation of Electrical Measurement is one of the subjects taught in the second semester at Physical Department of IKIP Mataram. One of the subjects is a single phase power measurement. But the fact is that in the laboratory of Physical Department at IKIP Mataram still not providing tool for learning activities in the form of wattmeter. This study aims to develop a scientific jobsheet to measure a single phase electric power-assisted 3 pieces voltmeter as modifying the wattmeter. This research included in type of research and development in three stages: preliminary studies, design development, and test media. Subjects were students of the second semester Department of Physics of IKIP Mataram who are studying the subjects. The application of problem based learning models that are used to raise the authentic issue of energy-saving lamp power measurement that common released on the market. Based on the data analysis can be concluded that: (1) a single-phase power measurement can be carried out using 3 voltmeter and (2) the reduction occurred in the power absorption of the energy-saving lamp tested than the original 5 watts to 1.8 watts.